Efficacy of low‐intensity extracorporeal shock wave therapy for the treatment of chronic prostatitis/chronic pelvic pain syndrome: A systematic review and meta‐analysis. Issue 6 (29th April 2019) - Yuan, Penghui; Ma, Delin; Zhang, Yucong; Gao, Xintao; Liu, Zhuo; Li, Rui; Wang, Tao; Wang, Shaogang; Liu, Jihong; Liu, Xiaming
Abstract: Aims: Low‐intensity extracorporeal shock wave therapy (Li‐ESWT) has been applied in urolithiasis and some chronic diseases. We performed a systematic review and meta‐analysis to assess the efficacy of Li‐ESWT for the treatment of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS). Methods: A comprehensive search of MEDLINE, Web of Science, EMBASE, and the Cochrane Library to January 6, 2019 was performed for randomized controlled trials (RCTs) reporting on patients with CP/CPPS treated with Li‐ESWT compared with the sham group. Outcomes were evaluated based on the National Institutes of Health Chronic Prostatitis Symptom Index (NIH‐CPSI). The quality assessment of included studies was performed by the Cochrane System. Results: Six publications involving five RCTs with 280 patients were assessed in this review. NIH‐CPSI total score, pain domain and quality of life (QOL) were significantly better in the Li‐ESWT group than those in the control group at the endpoint ( P < 0.00001, P = 0.003, and P < 0.00001), 4 weeks ( P < 0.00001, P = 0.0002 and P < 0.00001) and 12 weeks ( P < 0.00001, P < 0.00001, and P = 0.0002) after the treatment. For urinary score, significant difference existed at 12 weeks after the treatment ( P = 0.006). At 24 weeks after treatment, there was no significant difference between the two groups in NIH‐CPSI total score ( P = 0.26), pain domain ( P = 0.32), urinary score ( P = 0.07), and QOL ( P = 0.29). Conclusions: Li‐ESWT showed great efficacy for the treatment of CP/CPPS at the endpoint and during the follow‐up of 4 and 12 weeks, though the efficacy of 24‐week follow‐up was not significantly different due to insufficient data. Generally, Li‐ESWT is a promising minimal invasive method for the treatment of CP/CPPS.